Effects of perceptual-cognitive tasks on inter-joint coordination of soccer players and ordinary college students - Ren, Yuanyuan; Wang, Cenyi; Lu, Aming (Frontiers in Psychology, 2022)
Perceptual-cognitive tasks play a pivotal role in performing voluntary movements, which is crucial for good performances among soccer players. This study explored the effect of perceptual-cognitive tasks on the inter-joint coordination of soccer players and college students during landing. The classic multiple objective tracking (MOT) task was used to simulate the perceptual-cognitive task under a sports environment. Fifteen soccer players (age: 20.1 ± 1.5 yr, height: 181.4 ± 7.4 cm, weight: 75.4 ± 10.7 kg) and twenty ordinary college students (age: 20.0 ± 2.3 yr, height: 177.9 ± 4.9 cm, weight: 71.6 ± 9.9 kg) were enrolled to the study. Participants in the two groups were subjected to a single task (landing task) and dual-task (MOT task and landing task). Coordination and variability indicators were recorded using a Vicon infrared motion capture system and a force measuring platform. The results showed that the mean absolute relative phase of hip and knee joint (MARPhip-knee), deviation phase of hip and knee joint (DPhip-knee), and deviation phase of knee and ankle joint (DPknee-ankle) of the two groups under the dual-task were significantly different compared with the parameters when participants were subjected to the single task. The dual-task had higher effect size on DPhip-Knee and MARPhip-knee, indicating that dual-task had a greater impact on coordination of the hip and knee joints. DPhip-knee and DPknee-ankle of ordinary students were more extensive relative to those of the soccer players, and hip joint stiffness (Khip) for ordinary students was lower than that of the soccer players under the different tasks. These findings implied that the perceptual-cognitive task markedly affected the inter-joint coordination of soccer players and college students, mainly by impairing the hip and knee coordination. Although there is less variability in lower extremity coordination patterns of soccer players compared to college students, the MOT task still affects their coordination ability.